GE_GERICHTE P/19465/2021 vom 29. April 2024 - GE Cour de justice (2024)
PRÉSOMPTION D'INNOCENCE;VIOLATION DES DEVOIRS EN CAS D'ACCIDENT;DÉLIT DE FUITE | LCR.92.al2; LCR.96.al2; LCR.96.al1.leta; LCR.91a.al1